PERAN PENDIDIKAN ISLAM DI SMA MUHAMMADIYAH 3 SURAKARTA DALAM UPAYA PEMBENTUKAN AKHLAK DAN KARAKTER - Aprilia Indah Dwi Pawestri; Efri Roziati (Buletin Literasi Budaya Sekolah, 2023)
The formation of noble human beings is one of the essences of the goals of national education. However, at present, some of the younger generations are experiencing various symptoms of moral decline as a result of the alarming excesses of the modernization era. Teenagers are often still in an unstable psychological state. The same psychological condition is also manifested in fragile religious life, causing uncertainty, worry, and internal conflict. SMA Muhammadiyah 3 Surakarta is a private school engaged in the field of Islam and Muhammadiyah. This school tries to improve the morals and character of students through the role of Islamic education based on the Quran and Sunnah. This research uses descriptive qualitative methods with data collection techniques in the form of observation, interviews and documentation. Based on the results and discussions that have been described, it can be concluded that the role of Islamic education in efforts to shape the morals and character of students is divided into several effective habituation programs. The existence of this habituation can form morals and characters that make an impression on students and are more meaningful.